The marketing environment - Blythe, James (Henry Stewart Talks, 2012)
Classifying environmental factors, Influence of Governments, Economic factors in the environment, Socio-cultural issues, Technological factors, Legal factors in the environment, Environmentalism and the marketing environment, Influencing the macro-environment, The competitive environment, The industry environment, The customer environment, Staff relationships, Corporate culture, Resource constraints